COMPUTERIZED NEW STUDENT RECEPTION IN GOOD BUSINESS IN PART SDK. HOPE THE AGE - Dina Herlina; Irwan Bastian, Skom., MM (Jurnal Sistem Informasi, 2000)
This writing discusses the problems that arise on the part of Administration SDK. Age of hope with the old system. From this analysis, the computerized to save student data is necessary so that data processing can be more effective and efficient.